Factores de manejo que afectan los rendimentos de los cerdos posdetete - Campabadal Herrero, Carlos (Universidad de Costa Rica, 2013)
Factors affecting baby pigs postweaning performance. Management postweaning is one of the most critical factor that affect future pig performance. Two main factors affecting the animal performance are the body weight at weaning and the environment. Lighter body weights animals obtained Iower gains and less efficient feed conversion at the same age of weaning. The environmental factors are those afected by the climate, social status and type of facilities. In relation to the climate, room temperature, air draught, ventilation, cleanness and wet floors are the most importante factors. Temperatures between 28 and 30 Co are the most convenient for the period two weeks after weaning. Temperatures below 24 Co causes diarrhea and low performance. The social environment is determined by the pig social order mixture of litters, size and weight of the groups, the floor space allowances and the size and type of feeders. The type of facilities include all-in all out, three side productions and the type of floor and pens.